Respon Pertumbuhan dan Hasil Tanaman Packcoy (Brassica rapa L.) Terhadap Pemberian Dosis Biochar Sekam Padi - Putu Lasmi Yuliyanti Sapanca; Ramdhoani; Alfianus Galus (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
The packcoy plant is one of the vegetable plants that is in great demand by the public today because the price is relatively cheap and this vegetable is easy to process into vegetables compared to other types of vegetables. The purpose of this study was to determine the effect of doses of rice husk biochar on the growth and yield of packcoy (Brassica rapa L.) and to determine the best dosage of rice husk biochar on the growth and yield of packcoy (Brassica rapa L.). This research was conducted in the Kalpatarugarden, Jln Sedap Malam, Sanur, South Denpasar. This research was conducted from March to May 2023. The data obtained was analyzed using analysis of variance according to the design used, namely Randomized Block Design (RBD). If the analysis of variance shows a significant to very real effect. Then it will be continued with the Least Significant Difference Test (5% BNT). The results showed that the administration of rice husk biochar had a very significant effect on the growth and yield of mustard greens (Brassica rapa L.). The best concentration of rice husk biochar on the growth and yield of pokcay plants was the treatment of 400 g of biochar/10 kg of soil.